Pergeseran Nilai-Nilai Budaya dalam Kehidupan Masyarakat Desa Kauditan 1 Kabupaten Minahasa Utara: Kajian Tentang Pergeseran Nilai-Nilai Budaya Mapalus - Katuuk, Dessy Trully Caterine; Kerebungu, Ferdinand; Pangkey, Itje; Tuerah, Paulus R. (Abdurrauf Science and Society, 2025)
This research examines the shift of Mapalus cultural values in the life of the people of Kauditan 1 Village, North Minahasa Regency. The focus of the research includes identification of Mapalus values, analysis of its shift, and efforts to preserve it. Qualitative research method with the determination of research subjects by purposive method. Data collection techniques are observation, interviews, documentation using qualitative analysis according to Milles and Hubberman. The research results are as follows: 1) The types of Mapalus activities that exist in the life of the Kauditan 1 Village community, namely: Mapalus activities in farming, Mapalus activities in social life: helping when there is a natural disaster, death, or accident, Mapalus activities in building houses, repairing roofs, digging wells, Mapalus activities in terms of parties, such as weddings, circumcisions, and Mapalus activities to make irrigation, bridges, and build or repair roads. 2) Mapalus culture that is considered important in the life of the community, namely: Mapalus farming, Mapalus culture in social activities such as death, marriage, and repairing public facilities or what is known as social service. 3) Shifts or changes in cultural values in Mapalus activities, namely Changes in Mapalus work replaced with money (paying services and wages), The existence of organic solidarity, which considers hiring labour more practical, The fading of the value of togetherness in society, and Changes in social behaviour, and 4) Efforts to preserve cultural values in Mapalus or mapalus activities in community life, namely: as follows: a) Providing learning mapalus values to the general public, b) Socialisation process to the community about the values of togetherness, c) Strengthening existing Mapalus or mapalus activities, and d) Reviving Mapalus or mapalus activities. Abstrak: Penelitian ini mengkaji pergeseran nilai-nilai budaya mapalus dalam kehidupan masyarakat Desa Kauditan 1 Kabupaten Minahasa Utara. Fokus penelitian meliputi identifikasi nilai-nilai Mapalus, analisis pergeserannya, dan upaya pelestariannya. Metode penelitian kualitatif dengan penentuan subyek penelitian dengan cara pusposive. Teknik pengumpulan data yakni observasi, wawancara, dokumentasi menggunakan analisis kualitatif menurut Milles dan Hubberman. Hasil penelitian sebagai berikut: 1) Jenis-jenis kegiatan mapalus yang ada dalam kehidupan masyarakat desa kauditan 1, yakni: kegiatan mapalus dalam bercocok tanam, kegiatan mapalus dalam kehidupan sosial: membantu saat ada bencana alam, kematian, atau kecelakaan, kegiatan mapalus dalam membangun rumah, memperbaiki atap, menggali sumur, kegiatan mapalus dalam hal pesta, seperti pernikahan, khitanan, dan kegiatan mapalus membuat irigasi, jembatan, dan membangun ataupun memperbaiki jalan. 2) Budaya mapalus yang dianggap penting dalam kehidupan masyarakat yakni: mapalus bercocok tanam, budaya mapalus dalam kegiatan sosial seperti kematian, pernikahan, dan memperbaiki fasilitas umum atau yang dikenal dengan kerja bakti sosial. 3) Pergeseran atau perubahan nilai-nilai budaya dalam kegiatan mapalus yakni terjadi perubahan kerja mapalus diganti dengan uang (membayar jasa dan upah), adanya solidaritas organik, yang menganggap sewa buruh lebih praktis, lunturnya nilai kebersamaan dalam masyarakat, dan perubahan perilaku sosial, dan 4) Usaha melestarikan nilai- nilai budaya dalam kegiatan mapalus atau mapalus dalam kehidupan bermasyarakat yakni: a) Pemberian pembelajaran nilai-nilai mapalus pada masyarakat umum, b) Proses sosialisasi kepada masyarakat tentang nilai-nilai kebersamaan, c) Penguatan kegiatan mapalus atau mapalus yang ada, dan d) menghidupkan kegiatan mapalus atau mapalus. Kata kunci: Pergeseran nilai, Nilai budaya, Mapalus